27 Creation of a Physiotherapy Student Workbook. (14th March 2023) - Perkins, Nicola; Davies, Gwenllian; Baker, Idris
Abstract : Background: The Specialist Palliative Care (SPC) Physiotherapy team frequently host third year Physiotherapy Students from Cardiff University for clinical placements. The students understanding of Palliative Care was generally very limited and variable. It was thought that a Student Workbook would benefit both the students and SPC Physiotherapy clinical educators in order to provide guidance for self-directed study and evidence for grading at the end of the placement. Method: A student workbook was created, to be issued to students at the beginning of their placement and then reviewed during their end of placement feedback session. The workbook covers pertinent topics to guide student self-study and clinical practice within SPC, including syringe drivers, goal setting, metastatic spinal cord compressions and 'Total pain'. Each topic ends with prompts and questions for the student to research and consider independently. The workbook is issued to all Cardiff University Physiotherapy Students completing a SPC clinical placement and is also being issued by Chichester University to its Physiotherapy students. Results: Feedback has been obtained from past Students, and staff at Chichester University, and is positive and supportive of the use of the workbook. '…Very helpful in giving me an overview of the palliative care setting and a guide for my self-study' '…Opened the door for a more targeted self-study plan' '…gave me better clinical understanding and judgement of the physio role in palliative care' '…really enjoyed the workbook' 'Excellent feedback' (given to Senior PT Lecturer from students). 'Extremely valuable' Conclusions: Pt students' prior knowledge of SPC and the role of PT in SPC was limited and variable. A Student workbook was created and is issued to all students attending on clinical placement and is also circulated to Physiotherapy Students in Chichester University. Feedback from both University staff and students has been positive and supportive.